LA MORT DE PAUVRES AND LES ENFANTS PAUVRES BY CHARLES BAUDELAIRE AND VICTOR HUGO (A COMPARATIVE STUDY) - Verra Manangkot (Universitas Negeri Manado, 2022)
This study aims to examine the intrinsic elements in terms of the nature of the poems La Mort Des Pauvres and Les Enfants Pauvres. Characterizing the similarities and differences between the two poems in terms of the essence of poetry serves to be the focus of this study. The method used is descriptive qualitative method using a semiotic structuralism approach. Data collection in this study was carried out in two ways according to the object to be studied. First, by collecting literary materials, in this case the poems of La Mort Des Pauvres and the poems of Les Enfants Pauvres which will be studied. After that, the listening method is used, a technique by letting the informant intuitively determine certain literary elements as aesthetic elements contained in poetry. The results of the research Poetry 'La mort des pauvres' has the theme of failure, and sees that only death can end all failure, gloom and suffering of the life of the poor, while the poem, 'Les enfants pauvres' with the theme of God and humanity shows that the poet is a religious person. Meanwhile, through the poem 'Les enfants pauvres' the poet wants to give messages and appeals to human beings who have a sense of humanity and are obliged to love, respect, and protect those around us.